2016
DOI: 10.1007/s11906-015-0610-9
|View full text |Cite
|
Sign up to set email alerts
|

Renal Denervation for Treatment of Hypertension: a Second Start and New Challenges

Abstract: Following the publication of the randomized controlled but open-label trial Symplicity HTN-2, catheter-based renal sympathetic denervation was proposed as a novel treatment for drug-resistant hypertension. Thousands of procedures were routinely performed in Europe, Australia and Asia, and many observational studies were published. A sudden shift from overoptimistic views to radical scepticism occurred later, when the large US randomized sham-controlled trial Symplicity HTN-3 failed to meet its primary blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 89 publications
1
14
0
1
Order By: Relevance
“…Various factors might explain the considerable heterogeneity in the effects of RDN on BP. Newer studies aim to avoid the confounding effects of BP lowering drugs and the variation in adherence to medical treatment [27]. At this point, the results of the proof-of-concept trial SPYRAL HTN-OFF MED suggest efficacy of RDN on BP in the absence of antihypertensive medications [13, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Various factors might explain the considerable heterogeneity in the effects of RDN on BP. Newer studies aim to avoid the confounding effects of BP lowering drugs and the variation in adherence to medical treatment [27]. At this point, the results of the proof-of-concept trial SPYRAL HTN-OFF MED suggest efficacy of RDN on BP in the absence of antihypertensive medications [13, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Male sex, baseline daytime ambulatory systolic BP (SBP), baseline nighttime ambulatory SBP and its standard deviation, changes in daytime ambulatory heart rate, low treatment score, high adherence to SSHAT were independently associated with the BP response, whereas ethnic origin and the number of ablations were not . Nevertheless, identification of predictive factors of BP response to RDN is still necessary to facilitate the selection of patients likely to benefit most from this invasive procedure …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Nevertheless, identification of predictive factors of BP response to RDN is still necessary to facilitate the selection of patients likely to benefit most from this invasive procedure. 4,5 The presence of abdominal aortic calcifications (AAC) is associated with greater aortic stiffness 6,7 and a poorer hemodynamic response to antihypertensive drugs. 8 However, it is unknown whether the loss of the viscoelastic and biomechanical properties of the aorta associated with AAC also affects the systemic and renal hemodynamic response to RDN in patients with resistant hypertension.…”
mentioning
confidence: 99%
“…[15,16] Or it could be the other way around those patients with low calcium scores will not respond to RDN because of inadequate catheter – renal nerve tissue contact due to for example noncalcified atherosclerotic plaques or large distance from endovascular wall to the nerve tissue in the adventitia which might lead to inadequate ablations. [17] Vink et al [18] have shown that RDN does not always result in circular lesions completely destroying the renal nerves. These considerations highlight, apart from exploring predictors of response, the need for a clear procedural end point of RDN.…”
Section: Discussionmentioning
confidence: 99%